Soil biological indicators associated to the phosphorus cycle in a Cerrado soil under no-till and conventional tillage systems - Carneiro, Roberto Guimarães; Mendes, Iêda de Carvalho; Lovato, Paulo Emílio; Carvalho, Arminda Moreira; Vivaldi, Lúcio José (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the effects of no-till, conventional tillage and cover crops on biological indicators associated to the P cycle. The work was carried out on three adjacent areas on a Red-Yellow Oxisol: area I, a two-year experiment comparing the two management systems; area II, a six-year experiment, and area III, a native Cerrado vegetation. The soil was sampled at two depths (0–5 cm and 5–20 cm) in July/1998 and January/1999. The biological indicators evaluated were microbial biomass P, acid phosphatase activity, phosphate-solubilizing and total soil fungi and bacteria. Acid phosphatase activity and number of phosphate-solubilizing microorganisms, at the 0–5 cm depth, were significantly greater in the no-till soil, as compared to the conventional tillage. Differences between the tillage systems, regarding the biological indicators evaluated, were more pronounced in area II in which the no-till system had been established for a longer period. Microbial P decreased in the no-till Raphanus sativus treatment. P-solubilizing fungi increased in the presence of Cajanus cajan and Raphanus sativus, whereas the P-solubilizing bacteria increased in the presence of C. cajan. Highest activities of acid phosphatase were detected in the soil under native vegetation, evidencing the importance of organic P mineralization in this ecosystem.